Spartengewerkschaften auch in Wettbewerbsbereichen unterbinden - Horst Zimmermann (Wirtschaftsdienst, 2016)
Das Bundesverfassungsgericht ist derzeit mit der Zulässigkeit von Spartengewerkschaften befasst. Dabei ist es wichtig, neben den dort behandelten juristischen Argumenten auch die ökonomische Sinnhaftigkeit von Spartengewerkschaften zu analysieren. Dazu untersucht Horst Zimmermann die Anreizstruktur der Spartengewerkschaften. Das Ergebnis deutet auf starke und zunehmende Missbrauchsmöglichkeiten hin und führt zu der Folgerung, dass Spartengewerkschaften generell zu unterbinden sind. – – Craft unions are trade unions which represent a specific professional branch of the workforce. The German Constitutional Court is currently examining a new law which would more or less stop their activities. This paper argues in favour of such restriction, not only in protected sectors with price regulation, public bail outs, etc. (as a previous paper did), but also in competitive sectors of the economy like airlines. The reason is that craft unions abuse monopolistic bottlenecks to siphon off economic rents at the cost of their colleagues, which simultaneously hurts efficiency and equity. Moreover, there is no indication that these adverse incentives diminish over time.
Keywords: J5; K31; L93; 330